Intraoperative seizures in supratentorial surgery: A series of 60 cases at a single centre. Issue 1 (January 2019) - Rinaldo, S.; Devigili, G.; Di Meco, F.; Franzini, A.; Ferroli, P.; Eleopra, R.
Abstract : In supratentorial neurosurgery cortical functional mapping and monitoring of motor pathways has been demonstrated useful. Seizures are the most common side effect of electrical brain stimulation. Aim of our collection is to report occurrence of intraoperative seizures in patients underwent to supratentorial surgery at our centre in the last five months. We collected the following data: demographic, seizures and AED before surgery, during IOM and in the early post-operative phase up to discharge. We evaluated, during IOM: EEG; EMG; SEPs; MEP-TES ; MEP-DES ; DCS (bipolar/language or monopolar/motor). Sixty patients enrolled: 25 female, 35 male (mean age 49 years). 42% of patient had no seizures before surgery. At the hospital admission, 34% were without AED. Intraoperative EEG shows sharped activity, not related to stimulation, in 5 cases. Monopolar stimulation was performed in 87% of cases. Ojemann in awake (15%). DCS for motor pathways monitoring in 77% of surgeries. One intraoperative seizure, unrelated to the stimulation, was detected in a patient with recidive hypothalamic pilocytic astrocytoma. In two cases occurred seizures in the early post-operative period. The DCS with continue EEG intraoperative monitoring, an accurate seizures and AED history collection gives useful instrument to tailored selective stimulation.